Are the grandparents alright? The health consequences of grandparental childcare provision - Peter Eibich; Xianhua Zai (Journal of Population Economics, 2024)
This paper examines the causal effect of childcare provision on grandparents' health in the United States. We use the sex ratio among older adults' children as an instrument for grandparental childcare provision. Our instrument exploits that parents of daughters transition to grandparenthood earlier and invest more in their grandchildren than parents of sons. We estimate 2SLS regressions using data from the Health and Retirement Study. The results suggest that providing childcare is detrimental to grandparents' physical functioning and subjective health. We show that these effects increase with the intensity of grandchild care provision, and the effects are driven primarily by grandmothers.
Keywords: I10; J13; J14; C26; 330; Grandparents; Childcare provision; Instrumental variables; Health